Analisis Bisnis Dan Marketing Dalam Islam - Vilencia, Vilencia; Reani, Eva; Br. Sembiring, Marlena (Al-Sharf: Jurnal Ekonomi Islam, 2020)
This research was conducted to obtain information about business and marketing in Islam which is used by entrepreneurs in market competition and to increase income. The research conducted is a qualitative research type with descriptive form and the subjects used as sources in the research are entrepreneurs and businessmen consisting of several informants who meet interview techniques that can INTERVIEW and DOCUMENTATION and data analysis using SWOT analysis. Marketing data analysis is a technique of retrieving information available in the market to form the basis for creating a marketing strategy for a business. This analysis is an important part of every business, because it can show the performance of your business in the market so far. All this information is obtained from all marketing channels and then consolidated to produce one marketing view. Predicting the future can be done through marketing data analysis such as finding out what trends will prevail, which markets will grow fast and making assumptions about these findings. This makes it easier for your company to determine the right marketing plan for the future. Customer loyalty and ROI that can affect your current market as well as the future of your company.keyword: Bisnis dan Marketing